2009
DOI: 10.1089/clo.2009.0028
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Starved Apoptotic Fibroblasts Reduce Blastocyst Production but Enable Development to Term after SCNT in Cattle

Abstract: Cell cycle synchronization by serum starvation (SS) induces apoptosis in somatic cells. This side effect of SS is hypothesized to negatively affect the outcome of somatic cell nuclear transfer (SCNT). We determined whether apoptotic fibroblasts affect SCNT yields. Serum-starved, adult, bovine fibroblasts were stained with annexin V-FITC/propidium iodide to allow apoptosis detection by flow cytometry. Positive and negative cells sorted by fluorescence activated cell sorting (FACS) and an unsorted control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 48 publications
0
13
0
2
Order By: Relevance
“…This may be attributed to the induction of apoptosis, which affected the development of cloned embryos. Miranda et al (2009) showed that blastocyst production and quality after SCNT were reduced using apoptotic cells induced by serum starvation. Park et al (2004) found that treatment of donor cells with putative apoptosis inhibitors reduced apoptosis after SCNT and improved the development of cloned embryos.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the induction of apoptosis, which affected the development of cloned embryos. Miranda et al (2009) showed that blastocyst production and quality after SCNT were reduced using apoptotic cells induced by serum starvation. Park et al (2004) found that treatment of donor cells with putative apoptosis inhibitors reduced apoptosis after SCNT and improved the development of cloned embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Since all doses resulted in significantly higher proliferation/viability according to the MTT assay, 2 mM of VPA was used in the subsequent experiments as this concentration has been shown to increase the rates of induced pluripotent stem cells (iPSCs) [21] production and SCNT in mice [14]. It is noteworthy that based on the MTT assay, the treatment with VPA increased cell proliferation/viability while these cells were not expected to proliferate because of serum starvation to synchronize the cell cycle [46], [47]. However, this increase might be caused as a side effect of VPA on cell metabolism as the MTT assay is based on activity of metabolic enzymes that reduces tetrazolium salts [30].…”
Section: Discussionmentioning
confidence: 99%
“…The blastocysts produced from urine-and tail skin-derived cells were, however, of superior quality compared to those produced from ear skin cells, in terms of a lower AI. This could be due to a higher level of apoptosis in ear skin cells because the AI has been reported to be higher in bovine blastocysts derived from annexin-positive apoptotic cells than in those derived from annexin-negative nonapoptotic cells (Miranda Mdos et al, 2009). However, a lower level of apoptosis was not reflected in the relative transcript levels of proapoptotic genes CAS-PASE3 and CASPASE9 and in the expression level of P53, which were found to be similar among the blastocysts produced from the three types of cells.…”
Section: Urine-and Tail Skin-derived Cells For Scntmentioning
confidence: 99%